Russian diplomats in Spain and Antonio Ugarte (1812-1813): the controversial cooperation - E. E. Yurchik (Ибероамериканские тетради, 2023)
The article focuses on several cases in the history of Russian-Spanish diplomatic relations during the Spanish War of Independence, especially during the first year of the Alliance treaty between the two powers. Basing on the Russian and Spanish archives, the author studies the interaction of Pavel Mohrenheim and Yuly Wallenstein, Russian diplomats in Spain, with Antonio Ugarte y Larrazábal, the Spanish bureaucrat, responsible for the property and archive of the Russian mission in Madrid in 1812 – 1813. The article tends to reveal the characteristics of Russian diplomatic activity in the extraordinary war situation and in the absence of a plenipotentiary representative of Russia in Spain. The initial period of Russian-Spanish relations in the Iberian Peninsula after the conclusion of the treatise in Velikiye Luki is still presented in historiography in the most general form; the biographies and activities of its participants have not been studied in details. The primary sources used in the article enable to reconstruct the historical context and the relationship between Russian and Spanish diplomats, their perception of allied cooperation, and the obstacles they had to overcome. Thanks to the orders of Pavel Mohrenheim, the Chargé d’Affaires of Russia, given before his compelled departure from Spain, the interests of Russian Empire were ensured by balancing the official activities of the Spanish representative and the activity of the Russian agent Wallenstein, whose diplomatic status was doubtful. Ugarte, a trustee of the Russian mission, was guided by the instructions of the Regency Council and sought to establish his monopoly on the affairs of the Russian mission, including informing the Government of the Russian empire about the situation in Spain. Despite the personal rivalry between the Russian and Spanish representatives, both sides managed to avoid conflict and created the basis for the development of allied relations between Spain and Russia.